TOXIC SYMPTOMS IN WISTAR STRAIN RATS ON SINGLE AND REPEATED DOSAGE FROM THE EXTRACT OF RED BETEL LEAF (Piper crocatum) AS A TOXICITY TEST OF PERIODONTAL POCKET THERAPY - Dewi Lidya Ichwana; Herryawan (Journal of Health and Dental Sciences, 2023)
Red betel leaf (Piper crocatum) is one of the potential medicinal plants known to have properties to cure various diseases. The main components of betel leaf exhibit antiseptic, bactericidal, and antioxidant effects. The betel leaf was concentrated into an essential oil containing the antiseptic chemical. The antibacterial power of betel leaf essential oil is due to the content of phenolic compounds and their derivatives that can denature bacterial cell proteins, so it was considered to have potential as a material that could develop for periodontal therapy. After going through the stages of toxicity testing and repeated dose in terms of mortality, changes in body weight, and relative organ index of Wistar strain rats, the study continued to observe the effects that occurred after using single and repeated doses of 100, 400, and 1000 mg/kg BW in vivo using red betel leaf extract with the parameters of observing the behavior of rats studied for 14 days. Observation of the behavior of the test animals on toxic symptoms at each visit consisted of motor activity, straub phenomenon, piloerection, ptosis, corneal reflex, pineal reflex, lacrimation, vasodilation, catalepsy, dangling, reestablishment, walking backwards, circular walking, flexion, haffner, writhing, grooming, tremor, body shaking, vocalizations, urination, defecation, heart rate, salivation, mortality, posture, and breath changes before and after dosing for 14 days. From the observations, the analysis of the data obtained is primary data. Primary data in the form of qualitative data was obtained from data on effects that occurred after the rats were given a dose. After processing the data, the data is presented in tabular and narrative form based on the observations by showing the test dose used, the number of animals showing a toxic effect, the time of onset of a toxic effect and the percentage of animals in a group showing a toxic result. Based on the results of the study, red betel leaf extract with doses of 100, 400, and 1,000 mg/kg BW which was observed on the first and 14th days, did not cause toxic symptoms in all groups of rats, both on single administration and repeated administration for 14 days. DOI : 10.54052/jhds.v2n3.p439-454